PEMBENTUKAN PERATURAN DAERAH YANG BAIK SEBAGAI SARANA MEWUJUDKAN TUJUAN OTONOMI DAERAH - Dayanto Dayanto (IAIN Ambon, 2013)
The regional regulation is a product of regional legislation in accordance with the scope of regional autonomy in terms of self-regulation on the domestic affairs in the frame of unitary state of Indonesia in accordance with the mandate of regional autonomy as stipulated in the Acts RI No. 32, 2004 on the Regional Government. However, in reality, the establishment practice of regional regulation still shows the existence of regional regulation products which categorized as problematic regional regulation that contradictory to the goals to be achieved by the regional autonomy policy. Therefore, it is necessary formulation of good regional regulation based on the arrangement foundation and a proper preparation. Keywords: regional regulations, regional autonomy